MANAJEMEN PEMANFAATAN FAKTOR PRODUKSI KARET DI KECAMATAN SAMATIGA - Yasrizal Yasrizal (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2018)
AbstractAbstract: Keret plants are one of the commodities of the plantation sector and the largest contributor to PRDB in Aceh Province after oil palm. The statistics center noted that there were 144,291 tons of rubber production in Aceh Province but its productivity was only 0.61 percent. The planned productivity of rubber plant production is caused by production factors that have not been maximized. This research is a primary research, which is the population and sample in this study are all rubber farmers and entrepreneurs in Samatiga District, West Aceh. Data analysis uses a method of analyzing descriptions about the development of production and using multiple linear regression methods for influence analysis. From the results of the research, it can be concluded that the land area and capital have a positive and significant effect on rubber production in Samatiga, the variable that has the greatest influence on rubber production is the use of capital which includes the use of fertilizers and the use of superior seeds.key words: Rubber Production, Land Area and capital